Hydrolyzed polyacrylamide biotransformation during the formation of anode biofilm in microbial fuel cell biosystem: Bioelectricity, metabolites and functional microorganisms. (September 2022) - Zhao, Lanmei; Zhao, Dong
Graphical abstract: Highlights: Current density, voltage and power density rose with biofilm thickness. Bioelectricity production was related to HPAM (C/N) bioconversion. Laccase as a key enzyme induced HPAM metabolism and bioelectricity generation. Proteins from EPS induced by HPAM metabolism were conducive to forming biofilm. Microbial functions of C/N metabolism and bioelectricity production were clarified. Abstract: The anode biofilm serves as the core dominating the performance of microbial fuel cell (MFC) biosystem. This research provides new insights into hydrolyzed polyacrylamide (HPAM) biotransformation during the formation of anode biofilm. The current density, coulombic efficiency, voltage, power density, volatile fatty acid (VFA) production and total nitrogen (TN) removal enhanced with the thickening of biofilm (1–6 cm), and the maximums achieved 146 mA·m −2, 47.3%, 8.76 V, 1.28 W·m −2, 184 mg·L −1 and 84.6%, respectively. HPAM concentration descended from 508 mg·L −1 to 83.3 mg·L −1 after 60 days. HPAM was metabolized into VFAs, N2, NO2 – -N and NO3 – -N, thereby releasing electrons. Laccase and tyrosine/tryptophan protein induced HPAM metabolism and bioelectricity production. The microbial functions involving HPAM biotransformation and bioelectricity generation were clarified. The alternative resource recovery, techno-economic comparison and development direction of MFC biosystem were discussed to achieve the synchronization of HPAM-containing wastewater treatment and bioelectricity generation based on MFC biosystem.